2017
DOI: 10.1016/j.jcrs.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Depth of focus after implantation of spherical or aspheric intraocular lenses in hyperopic and emmetropic patients

Abstract: Implantation of a monofocal spherical IOL resulted in an increased depth of focus without significant degradation of distance visual acuity or contrast sensitivity. There were no differences in the depth of focus between hyperopic eyes and emmetropic eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Previous studies reported that spherical IOLs improve through-focus visual acuity compared to an aspheric monofocal IOL due to the increase of the total primary spherical aberration of the eye. 16,17 However, the effect of primary spherical aberration in through-focus performance is strongly dependent on pupil size and is associated with losses in contrast vision at distance. For large pupils, primary spherical aberration increases the depth of focus and reduces distance image quality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that spherical IOLs improve through-focus visual acuity compared to an aspheric monofocal IOL due to the increase of the total primary spherical aberration of the eye. 16,17 However, the effect of primary spherical aberration in through-focus performance is strongly dependent on pupil size and is associated with losses in contrast vision at distance. For large pupils, primary spherical aberration increases the depth of focus and reduces distance image quality.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations to the light adjustable IOL once implanted in the eye through UV radiation patterns can also create an EDOF effect (Villegas et al, 2014). There is also a pinhole iris-fixated IOL specifically designed to reduce dysphotopsia and photophobia (Munoz et al, 2015), which will extend the depth of focus as will any aspheric design (Steinwender et al, 2017). Hence, in 2016, the American Academy of Ophthalmology Task Force Consensus Statement on EDOF IOLs was published to provide minimum performance criteria to evaluate a device as having an EDOF performance under photopic, mesopic, and glare conditions based on testing vision at far and intermediate distances as well as defocus curve testing (MacRae et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…We eschewed an aspheric IOL because we surmised that positive spherical aberration supplied by a spherical IOL could have favourable effects on depth of field and intermediate vision while maintaining distance visual acuity and therefore increase binocular summation over a larger range of vision. 11,12 Thus, a spherical IOL may be paired with an EDOF-IOL, as the latter IOL provides an even greater depth of field. While spherical IOLs may have fallen out of favour for routine cataract surgery in modern practice, these properties mentioned above merit (re)consideration for their utility for presbyopia correction in conjunction with currently-available IOLs.…”
Section: Visual Acuitymentioning
confidence: 99%